Análise reflexiva e memorial sobre as atividades práticas do curso de medicina da Universidade Federal de São Carlos - Cruz, Zenedine Mariano Rocha da (Universidade Federal de São Carlos, 2022)
This work describes the itinerary of a student of the Medicine course at the Federal University of São Carlos from 2017 to 2023. It aims to demonstrate my vision on the stages experienced in the scope of my medical education. The narrative represents the Final Project, as foreseen in the Political Pedagogical Project, in the form of a critical-reflective memorial. Divided into cycles, it shows the path of a young Cape Verdean student, inserted in a singular pedagogical and social sphere, which is the medical course based on the active methodology PBL (Problem Based Learning) in the city of São Carlos, in the interior of São Paulo, Brazil. In this comment on the methodology that transformed my educational paradigm, PBL; I evoke memories of my arrival in Brazil and the importance of resilience to solve insecurities; I analyze the chronological moments of the course, called educational cycles, which are the milestones of the engagement, theoretical and practical deepening, maturity and successful use of the constructivist spiral for the construction of knowledge; I mention the period of electives, which are the periods legitimized to the student's will to engage in a new practical or theoretical activity of improvement or learning of more skills, an activity of great importance and symbol of a pioneering course.
Reflective analysis and memorial about the practical activities of the medical course at the Federal University of São Carlos
Keywords: Prática profissional; Metodologia ativa; Espiral construtivista; Professional practice; Active methodology; Constructivist spiral; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM